DASAR PEMIKIRAN IBNU MALIK DAN REPRESENTASI PEMIKIRAN BASRAH DALAM KITAB ALFIYAHNYA - Khairunnisa, Annisa; Pribadi, Mohammad; Sugiyono, Sugeng (STIQ Amuntai, 2024)
The basis for establishing the rules and forms of Ibn Malik's thought in the science of nahwu has a distinctive character. Therefore, this study has two aims, (1) to explicitly identify the basis of Ibn Malik in establishing nahwu rules in general. (2) examine the form of Ibn Malik's thought which tends towards the Basrah flow represented in the book of Alfiyah. The approach in this research is descriptive qualitative. The research data are facts related to Ibn Malik's thoughts, lingual units contained in the Alfiyah book, and information related to his interpretation. The data sources for this study are kitabs, books, scientific journals, and relevant research. The method for providing data is by observing techniques in the form of reading data, followed by a tapping process. The analysis method used is content analysis. The results of the research show that in establishing the rules of nahwu, Ibnu Malik used a different base of thought compared to previous nahwu scholars, namely referring to hadith extensively. This is based on his intellectual journey, his expertise in studying hadith, as well as the historical factor that hadith at that time had been well translated. As for the form of thought that tends towards the Basrah school, it is represented in one of his phenomenal books, namely Alfiyah. In this book have found 51 problems (the most dominant quantity) that tend to be based on Basrah's thinking, both in terms of the form of rules established and the framework of thinking.